Promise not kept: universal primary education for all children in sub-Saharan Africa - Birger Fredriksen (Emerald Publishing, 2023)
Purpose - This article examines why Universal Primary Education (UPE) has shifted from being a developing country challenge more broadly in the last half of the 20th century to become largely a sub-Saharan Africa (SSA) challenge today. It discusses a number of national and education sector system-wide challenges that have constrained the implementation of UPE in SSA more so than in other developing regions. Design/methodology/approach - This article reviews the literature and policy documents on a wide range of developing country issues, and discusses why most SSA countries have faced unparalleled challenges in achieving UPE. Findings - SSA governments should take the opportunity offered by their post-pandemic "build back better" efforts to fundamentally reset education policies to address the key causes of this major development failure. The overarching objective must be to develop education systems that are more inclusive, equitable and responsive to national development needs by better serving the large population groups, parts of society and economic sectors that currently derive little benefit from public education spending. This article highlights the urgency and challenges associated with achieving this objective. Originality/value - Although the main responsibility lies with SSA governments, this paper stresses that the global community will be affected in many ways by how effectively this crisis is addressed. Therefore, this effort merits sustained global support including through more catalytic use of aid.